Control of cell proliferation and elongation by miR396 - Ercoli, María Florencia (2016)
The combinatory effects of cell proliferation and cell elongation determines the rate at which organs growth. In the root meristematic zone cells both divide and expand, while post-mitotic cells in the elongation zone only expands until they reach their final size. The transcription factors of the GROWTH-REGULATING FACTOR (GRF) class promote cell proliferation in various plant organs. Their expression is restricted to cells with a high proliferative capacity, yet strong downregulation of the GRF activity compromise the plant survival. Part of expression pattern of the GRFs is ensured by the post-transcriptional repression mediated by the conserved microRNA miR396. Here we show the quantitative effects in root growth caused by GRF depletion in a series of transgenic lines with different miR396 levels. We show that high miRNA levels affect cell elongation and proliferation in roots. Detailed analysis suggests that cell proliferation is restricted due to a reduction in cell cycle speed that might result from defects in the accumulation of mitotic cyclins. The results provide insights into the participation of the miRNA-GRF regulatory network in root development.